The Effect of Think-Pair-Share Method and Inquiry Method on Intensive Reading Learning Outcomes Based on Learning Motivation Student Class Viii of Smpn 05 Linggo Sari Baganti Pesisir Selatan Regency - Rizcha Putri Stiffany; Atmazaki Atmazaki; Harris Effendi Thahar (Postgraduate School, Universitas Negeri Padang, 2020)
This research is motivated by students who have low reading ability. This study studied to study the differences in the results of intensive reading learning using Think-pair-share learning methods and Inquiry learning methods regarding learning motivation of VIII grade students of SMPN 05 Linggo Sari Baganti. This type of research is quantitative with a 2X2 factorial design. The results of the study are as follows. First, the value of intensive reading skills that use the Inquiry method is higher than the value of students who use the Think-Pair-Share method. Second, the value of students' intensive reading skills with high learning motivation using the Inquiry method is better than the value of students using the Think-Pair-Share method. Third, the value of students' reading ability that increases using the Inquiry learning method is better than the value of students who use Think-Pair-Share method. Fourth, there was no interaction between the Think-Pair-Share method and the Inquiry method with the motivation to learn about the reading skills of Grade VIII students of SMPN 05 Linggo Sari Baganti.